Hammocking: the effect of cushion covers on interface pressure measurements. - Crawford SA; Walsh DM; Porter-Armstrong AP (Disability & Rehabilitation: Assistive Technology)
Purpose. To investigate the effects of the cushion covers on interface pressure measurements using pressure mapping technology.Methods. Sixty-one healthy participants were recruited for laboratory-based study using single group design. Participants were pressure mapped on visco-elastic foam cushion and foam and fluid pack cushion with their covers on and with their covers removed. An air-filled cushion was tested with two different types of covers, an incontinence cover and 'Comfair' cover. Average and maximum pressures recorded at 6 mins by the Force Sensing Array pressure mapping system were used for statistical analysis.Results. There were no significant differences in maximum pressures for the three cushions tested with their covers on or with their covers removed. The cushion with the foam base and fluid pack did not demonstrate any significant differences in average pressure with the cover on or with the cover removed. However, the visco-elastic foam cushion showed significantly lower average pressures with the cover on (p = 0.019). The air-filled cushion showed lower average pressures with the incontinence cover on, when compared to the Comfair cover (p = 0.029).Conclusion. Contrary to the belief that the process of hammocking may create surface tension within the cushion covers, which in turn may adversely affect the cushions ability to reduce interface pressure, the cushions tested in the current study did not show significantly lower interface pressure measurements with the covers removed. Therefore the covers did not adversely affect the cushion's ability to reduce interface pressure. The findings of this study require verification with disabled clients.